HYDROLOGICAL RESPONSES OF RIVER BASINS TO LAND USE CHANGE IN SUSTAINABLE BUILT ENVIRONMENTS - Saputri, Utamy Sukmayu; Suripin; Wulandari, Dyah Ari; Moey, Lip Kean (International Journal on Livable Space, 2026)
Changes in land use, particularly the conversion of forests and agricultural land into urban settlements, alter hydrological responses by increasing runoff, raising peak discharge, and reducing baseflow. These changes affect flood risk, environmental quality, and the sustainability of built environments in rapidly urbanizing tropical regions. Aims: This study aims to systematically review applications of Soil and Water Assessment Tool (SWAT) and SWAT+ models to analyze hydrological responses to land use changes and evaluate their implications for urban flooding and sustainable built environments. Methodology and results: A Systematic Literature Review was conducted using Scopus-indexed and nationally accredited Indonesian journals. Studies were selected using keywords related to land use change, hydrological response, river basins, and SWAT or SWAT+ modelling. The results show that urbanization increases runoff, peak discharge, and sediment yield, while vegetation enhances infiltration and hydrological stability. Common parameters include streamflow, runoff, baseflow, and sediment yield. Performance is evaluated using NSE, R2, and PBIAS. Conclusion, significance and impact of the study: This review confirms that SWAT and SWAT+ support spatial planning and sustainable watershed management. It highlights the importance of integrating of hydrological modeling into land use planning to improve flood resilience and identifies gaps in future flood risk scenarios.